Multimode interference optical splitter based on photodefinable benzocyclobutene (BCB 4024-40) polymer - Ibrahim, Mohd Haniff; Lee, Shuh Ying; Chin, Mee Koy; Mohd. Kassim, Norazan; Mohammad, Abu Bakar (Society of Photo-Optical Instrumentation Engineers, 2007)
1×2 and 1×3 planar optical splitters based on Benzocyclobutene (BCB 4024-40) polymeric material are demonstrated for the first time. The devices are designed based on symmetric interference and fabricated on BK7 glass substrates with a thin layer of SiO2 as cover. A cost-effective chemical etching technique is used in the fabrication process to take advantage of the photosensitivity of the polymer. The waveguide loss was measured using the cutback method to be 3.5 dB/cm. The splitting uniformity is better than 0.02 and 1.5 dB at 1550-nm optical wavelength for the 1×2 and 1×3 splitters, respectively.